If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6g + -4h = k Solving 6g + -4h = k Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '4h' to each side of the equation. 6g + -4h + 4h = 4h + k Combine like terms: -4h + 4h = 0 6g + 0 = 4h + k 6g = 4h + k Divide each side by '6'. g = 0.6666666667h + 0.1666666667k Simplifying g = 0.6666666667h + 0.1666666667k
| 6x-9=4x-41 | | 3x^2+3x-30=0 | | 20b^2-9b=20 | | 42+j+18-19j=-28 | | 5x+7=3x+39 | | Bxt+c=a | | 2x+5+x=29 | | 3(-3)+7=-2 | | -3(x+4)=6-3x | | 8x-(4x-10)=14 | | A=3.6+c | | 4(6t-2)-7(12t-4)=-260 | | 3(x+5)-9=0 | | -7x-10=-17 | | .3x+x=34800 | | 2x^4-13x^3+20x^2=0 | | -3x+6=-6 | | 31-11x=11+9x | | B+2c-6=3c | | 3(x-5x)+2(xy+8x)+(-8xy)= | | 8=-2d | | 6z+7z=z-6+z | | 7(2x-4)=39 | | y-5=-(5+y) | | 7x+14=8x-48 | | 6-9x=5x-9x-24 | | (12x-7)-(5x-12)= | | 12p+5pd-3p+6pd= | | 4z-5z=5z-3-8z | | x+4+5x=22 | | 12y+36=36+12y | | 9a+74=20 |